Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.2147/ijgm.s42905
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension in the rural adult population of Osun State, southwestern Nigeria

Abstract: BackgroundThe purpose of this study was to determine the prevalence of hypertension in two rural communities of Osun State, Nigeria.MethodsA consenting adult population of the Alajue and Obokun rural communities in southwestern Nigeria that presented for the screening exercise participated in this community-based cross-sectional descriptive study. Two hundred and fifty-nine respondents aged older than 18 years completed a standardized, pretested, structured questionnaire as part of activities celebrating World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
16
4
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 29 publications
7
16
4
3
Order By: Relevance
“…This was unlike the results of Abu Sayeedet al 30 in Bangladesh and Asekun-Olarinmoyeet al 28 in Nigeria. Also, this study was inconsistent with that of Glewet al 31 in Nigeria where the normal average BP of 120/74mmHg was observed from the herdsmen.…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…This was unlike the results of Abu Sayeedet al 30 in Bangladesh and Asekun-Olarinmoyeet al 28 in Nigeria. Also, this study was inconsistent with that of Glewet al 31 in Nigeria where the normal average BP of 120/74mmHg was observed from the herdsmen.…”
Section: Resultscontrasting
confidence: 84%
“…This was lower as compared to the findings of AsekunOlarinmoyeet al 28 in Osun State, Nigeria who reported average age of about 49 years. However, this was comparable to the study of Addoet al 29 in Ghana with average age of 42 years among the rural communities.…”
Section: Resultscontrasting
confidence: 72%
“…Oladapo et al14 found a 20.8% prevalence of hypertension, while Onwubere et al,12 Asekun-Olarinmoye et al,18 Okeahialam et al,11 Onwuchekwa et al,19 Andy et al,20 and Ahaneku GI et al21 reported prevalence of 46.4%, 13.16%, 20.9%, 18.3%, 23.6%, and 44.5%, respectively, in their recent studies. These various studies on hypertension prevalence in Nigeria reported a wide range of prevalence rates using the BP cutoff point of 140/90 mmHg.…”
Section: Discussionmentioning
confidence: 96%
“…Já em países como a Nigéria e a China, a prevalência é de 66,7% e 56,5%, respectivamente, demonstrando que países em desenvolvimento apresentam prevalências de HAS bem mais elevadas do que as dos países de alta renda. 21,22 No presente estudo, a prevalência de HAS em idosos do sexo feminino foi significativamente maior que no sexo masculino em todos os anos avaliados. Diversos estudos demonstram que as mulheres procuram mais pelos serviços de saúde, aumentando suas chances de terem o diagnóstico de HAS, 8,11,13,23 além de afirmarem que mulheres, por terem maior sobrevida que homens, ficam mais propensas a sofrerem doenças crônicas.…”
Section: Discussionunclassified